2012
DOI: 10.1007/s11357-012-9496-5
|View full text |Cite
|
Sign up to set email alerts
|

A single administration of human umbilical cord blood T cells produces long-lasting effects in the aging hippocampus

Abstract: Neurogenesis occurs throughout life but significantly decreases with age. Human umbilical cord blood mononuclear cells (HUCB MNCs) have been shown to increase the proliferation of neural stem cells (NSCs) in the dentate gyrus (DG) of the hippocampus and the subgranular zone of aging rats (Bachstetter et al., BMC Neurosci 9:22, 2008), but it is unclear which fraction or combination of the HUCB MNCs are responsible for neurogenesis. To address this issue, we examined the ability of HUCB MNCs, CD4+, CD8+, CD3+, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 58 publications
4
22
0
Order By: Relevance
“…One study used umbilical cord blood demonstrating that a single injection was sufficient to increase neurogenesis in aged rats (Bachstetter et al 2008). A follow-up study examined which cells within the umbilical cord blood might be responsible, and it was suggested that naïve T cells were the fraction responsible for this effect (Shahaduzzaman et al 2013). Thus, it is clear that multiple factors and cells within young/ neonatal blood may have beneficial effects on the stem cell niches of aged subjects.…”
Section: Discussionmentioning
confidence: 99%
“…One study used umbilical cord blood demonstrating that a single injection was sufficient to increase neurogenesis in aged rats (Bachstetter et al 2008). A follow-up study examined which cells within the umbilical cord blood might be responsible, and it was suggested that naïve T cells were the fraction responsible for this effect (Shahaduzzaman et al 2013). Thus, it is clear that multiple factors and cells within young/ neonatal blood may have beneficial effects on the stem cell niches of aged subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all of the studies in the adult are in younger adults and not the aged. While the cells have a demonstrated ability to increase proliferation in the subgranular zone of the hippocampus and increase density of dendritic spines (Bachstetter et al 2008;Shahaduzzaman et al 2013) in the aged rat, they have not yet been shown to improve stroke outcome in an aged animal.…”
Section: Discussionmentioning
confidence: 99%
“…The cells also produce a number of molecules that are essential for the interaction of the cells with other cells and extracellular matrix, including E-selectin, L-selectin, intercellular adhesion molecule (ICAM), and vascular adhesion molecule (VCAM). While these adhesion molecules are essential for the trafficking of the UCB immune cells from the blood stream into the tissue, they may also be responsible for the ability of the UCB cells to enhance neuritic outgrowth in culture ) and stimulate dendritic growth in other animal models of CNS aging or disease (Shahaduzzaman et al 2013;Willing et al In Press).…”
Section: Cord Blood Cells Provide Trophic Supportmentioning
confidence: 99%
“…Furthermore, treatment with G-CSF has been shown to modulate neurogenesis in TBI and in other neurodegenerative disorders (e.g., hypoxic injury, Alzheimer’s disease, etc.) [75,77]. Our histological studies indicated that concomitant with functional improvement, adjunct treatment of G-CSF and hUCB resulted in more pronounced reduction of TBI-induced upregulation of MHCII + cells (putatively activated microglia) in the cortex, striatum, thalamus, SVZ, and the dentate gyrus (DG) of the hippocampus, compared with hUCB and/or G-CSF monotherapy [73].…”
Section: Combining G-csf and Stem Cells For Stroke Treatment: Translamentioning
confidence: 99%